THE EXTENDED URBANIZATION OF CAMERON HIGHLANDS: AN OPERATIONAL LANDSCAPE PERSPECTIVE - Amel Farhat, (Malaysian Journal of Tropical Geography (MJTG), 2025)
This study examines the transformation of Cameron Highlands, Malaysia, through the lens of extended urbanization, mobilizing the concepts of “operational landscapes” and “planetary urbanization” (Lefebvre, 1989; Brenner, 2014). It investigates how this former colonial hill station has evolved into a complex agrotourism destination, shaped by urban demands and global economic forces. Using a qualitative multi method approach, including field observations, interviews, and historical analysis, the study examines the working hypothesis that Cameron Highlands functions as an operational landscape that serves urban needs while being reshaped by urban influences, and evaluates this hypothesis through the triangulation of multiple qualitative data sources. The study finds that rapid development and commercialization have significantly altered the region's physical and cultural landscape, undermining its traditional appeal as a rural retreat. Key transformations include the 'plasticization' of the landscape, intensification of urban development, and erosion of the area's distinctive climate and character. These changes reflect broader processes of extended urbanization, where urban logics and practices extend far beyond conventional city boundaries. The research contributes to the theoretical discourse on operational landscapes by applying this framework to hill stations and agrotourism destinations. It also offers practical insights for sustainable development in areas experiencing rapid urbanization, highlighting the need for balanced approaches that consider both economic growth and environmental preservation in evolving operational landscapes.